2021
DOI: 10.1177/8756087920983551
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of Johnson-Segalman fluid in blade coating process

Abstract: This article deals with the blade coating process for Johnson-Segalman (JS) fluid using plane coater. Flow equations are simplified with the Lubrication approximation theory (LAT). The equations are normalized using suitable scales. Reduced equations are solved numerically using the shooting technique. Also, for small Weissenberg numbers, a perturbation solution is obtained. How Weissenberg number and slip parameter influence the pressure gradient, velocity, pressure, load, and thickness are expressed graphica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Atif et al 21 studied the Roll-over-web coating process of Rabinowitch model by using perturbation technique. Articles, [22][23][24][25][26] which analyzed various fluid models using a variety of solution methodologies under lubrication theory can be of interest to the readers.…”
Section: Introductionmentioning
confidence: 99%
“…Atif et al 21 studied the Roll-over-web coating process of Rabinowitch model by using perturbation technique. Articles, [22][23][24][25][26] which analyzed various fluid models using a variety of solution methodologies under lubrication theory can be of interest to the readers.…”
Section: Introductionmentioning
confidence: 99%
“…The JS fluid model is established by Ashraf et al [36] for evaluation of peristaltic-cilia flow inside human fallopian tube for development of embryo. Recently, Kanwal et al [37] proposed JS fluid model for the analysis of blade coating and utilized LAT for simplification of governing equations. They adopted perturbation method for attaining the solution and concluded that the load decreases as Weissenberg number increases however coating thickness increases in comparison of viscous case.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the pressure increases for the coupling number and micro-rotation parameter in comparison with Newtonian fluid, besides the coating thickness, as the coupling number increases. The analysis of Johnson-Segalman fluid is presented by Kanwal et al [26] for blade coating by considering plane coater. To simplify the governing flow equations, LAT has been adopted.…”
Section: Introductionmentioning
confidence: 99%